Severe edema after sclerotherapy of labial hemangioma with ethamolin oleate in a young child - De Queiroz, Sormani Bento Fernandes [UNESP]; De Lima, Valthierre Nunes [UNESP]; Amorim, Pedro Henrique GonÃ§alves Holanda; Statkievicz, Cristian [UNESP]; Magro-Filho, Osvaldo [UNESP] (Wolters Kluwer, 2016)
Adverse reactions related to ethanolamine oleate (EO) include pain during injection, redness, inflammation, tissue necrosis, and allergic reaction. The authors report a patient of exuberant facial edema after the injection of EO used in sclerotherapy of lip hemangioma in a child. A 9-year-old boy was referred to authors' oral and maxillofacial surgery unit to treat a vascular lesion of the upper lip. The lesion has causing enlargement of the middle area of the upper lip, being sessile and resilient by palpation. It was decided to employ sclerotherapy aiming to reduce the size for posterior surgical excision of the residual lesion. The day after the injection, the patient presented intense edema limited to the upper lip, complaining of mild pain. Although side effects reported of EO injection are mild and with almost no clinical significance, major complications like anaphylaxis and severe edema can occur, such in the patient here presented.
Keywords: Hamartoma; Hemangioma; Hemangiomas; Lobular Capillary; Oleic Acids; Sclerosing